1982
DOI: 10.1159/000145525
|View full text |Cite
|
Sign up to set email alerts
|

Histological Variations of Jejunal and Ileal Mucosa on Days 8 and 15 after Hypophysectomy in Rat: Morphometrical Analysis in Light and Electron Microscopy

Abstract: Variations of the intestinal mucosa were studied in male adult Wistar rats on day 8 and day 15 after hypophysectomy. All results were compared with those obtained in pair-fed control rats. Morphological variations were observed at two intestinal levels (high part [hp] and low part [lp] of the jejunoileum) both with morphometrical analysis (villous area, microvillous area, enterocytes, goblet and Paneth cell number, mitotic index...), in light or electron microscopy and with histochemical techniques (proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…18]. Thus repeated injections of somatostatin probably inhibit the intracellular synthesis of gastrin since we have never noticed any variations in light granules which would indicate associated modifications of the hormonal secretion [2]. But a more direct action of somatostatin might also be suspected as an early and significant de crease of labelling indexes was observed 2 h after the first injection of somatostatin.…”
Section: Discussionmentioning
confidence: 73%
“…18]. Thus repeated injections of somatostatin probably inhibit the intracellular synthesis of gastrin since we have never noticed any variations in light granules which would indicate associated modifications of the hormonal secretion [2]. But a more direct action of somatostatin might also be suspected as an early and significant de crease of labelling indexes was observed 2 h after the first injection of somatostatin.…”
Section: Discussionmentioning
confidence: 73%
“…Strong evidence has demonstrated that growth hormone (GH) is an important growth factor for intestine. Complete GH depletion due to hypophysectomy caused pronounced hypoplasia of small intestinal mucosa with decreased villus height and reduced crypt cell proliferation [36] . Simple replacement of GH can restore mucosal proliferative activity [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidences have demonstrated that growth hormone (GH) was an important growth factor for intestine [25] . Complete GH depletion due to hypophysectomy could cause pronounced hypoplasia of small intestinal mucosa with decreased villus height and reduced crypt cell proliferation [26] . Simple replacement of GH could restore mucosal proliferative activity [27] , rhGH could promote normal growth and development in the body by changing chemical activity in cells.…”
Section: Discussionmentioning
confidence: 99%